Pengaruh Corporate Governance Dan Kompensasi Rugi Fiskal Terhadap Tax Avoidance: Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bei Tahun 2017-2019 - Meiranti Andriyani; Endang Mahpudin (Jurnal Akuntansi dan Pajak, 2021)
Tax avoidance is a part of tax planning that is conducted legally. Tax Avoidance is conducted by the taxpayer (the company) to minimize the company's tax burden. The purpose of this research is to test how large the influence of corporate governance variables consist of institutional ownership, independent commissioner, audit quality, and audit committee and fiscal loss compensation variables in influencing tax evasion in mining companies listed on IDX (Indonesia Stock Exchange). The author uses secondary data of financial statements published by the mining companies listed on the IDX (Indonesia Stock Exchange). The results of this study indicate that the variables of institutional ownership, independent commissioner, and audit committee have significant influence on tax avoidance, while variable audit quality and fiscal loss compensation has no significant effect on tax avoidance on mining companies listed on the Indonesia Stock Exchange period 2017-2019. The samples used in this study were taken using the purposive sampling method. After a reduction with multiple criteria, set as many as 12 companies as samples. The analysis techniques on this study used a linear regression analysis with the help of SPSS 25 edition program.